Produção e qualidade de sementes de genótipos de lentilha em função de lâminas de irrigação - Arruda, Nathalya Vieira (2022)
To cultivate lentils in Brazil, the producer relies on manuals and works carried out in other regions of the world, mainly in Canada, where it is possible to find more detailed cultivation manuals. However, irrigation management varies according to genetic and environmental factors, and should be based on local recommendations for better productivity. Information of this type is precious and fundamental for the cultivation of lentils in Brazil. For this reason, the present project aims to define the most appropriate irrigation management for the lentil crop in Central Brazil, in addition to identifying genotypes more tolerant to water stress, to be used in the genetical enhancement program. The experiment was carried out from May to September 2021, in the experimental field of Embrapa Hortaliças. The experiment was carried out in a randomized block design (CBD), in a 5 x 3 factorial scheme, with two factors: factor 1 – irrigation replacement levels; and factor 2 – one cultivar (BRS Silvina) and two experimental lentil genotypes from Embrapa (G1 and G2). The productivity of the experiment was influenced by the irrigation depths, considering the isolated effect of the irrigation factor. Where the 125% depth with 1497.50 kg/ha differed from the 50% depth with 817.50 kg/ha, the others showed no statistical differences at 5%. Considering that no differences were observed between irrigation depths on seed weight, germination rate, emergence and aging of lentil seeds, these parameters do not help to choose an ideal irrigation depth. As well as the root length and number of branches. According to productivity and electrical conductivity, the water depth of 125% promoted greater seed productivity and vigor. As for the genotypes, only the G2 genotype showed differences in weight, seed conductivity and plant height lower than the others. Only in number of pods did G2 show higher values than the others.